2009
DOI: 10.1002/cyto.a.20827
|View full text |Cite
|
Sign up to set email alerts
|

Initial cytoplasmic and phagosomal consequences of human neutrophil exposure to Staphylococcus epidermidis

Abstract: Microorganisms are recognized by specific phagocyte surface receptors. Liganded receptors then signal a series of events leading to phagocytosis and destruction of the organism by oxidative, lytic, and associated processes. Some organisms, such as Mycobacterium tuberculosis (Mtb), Cryptococcus neoformans (Cf), and others, evade such destruction, surviving and sometimes multiplying within the phagosome to later cause disease. To study such evasion, we developed protocols which permit simultaneous kinetic measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…These inconsistent findings are likely to reflect methodological differences, as sample type (e.g., purified cells or whole blood), preparations and species of bacteria, together with the use of humoral factors (e.g., complement) vary considerably between studies (11). Although previous studies have utilized pHrodo as a tool for assessing phagocytosis, none have extended its use to simultaneous analysis of multiple cell types, or to whole blood assays (18,21). We found that preterm infants possess a decreased proportion of whole-blood phagocytes capable of phagocytosing the common neonatal pathogens SE, EC and, to a lesser extent, SA compared with term infants.…”
Section: Phagocytosis In Newborn Whole Bloodmentioning
confidence: 69%
See 3 more Smart Citations
“…These inconsistent findings are likely to reflect methodological differences, as sample type (e.g., purified cells or whole blood), preparations and species of bacteria, together with the use of humoral factors (e.g., complement) vary considerably between studies (11). Although previous studies have utilized pHrodo as a tool for assessing phagocytosis, none have extended its use to simultaneous analysis of multiple cell types, or to whole blood assays (18,21). We found that preterm infants possess a decreased proportion of whole-blood phagocytes capable of phagocytosing the common neonatal pathogens SE, EC and, to a lesser extent, SA compared with term infants.…”
Section: Phagocytosis In Newborn Whole Bloodmentioning
confidence: 69%
“…One possible caveat to these findings is the necessary use of heat-killed bacterial preparations, and commercially prepared SA and EC stocks that are non-neonatal sepsis isolates, which may influence interactions (33). Future studies could examine the real-time phagocytosis of live, neonatal bacterial isolates by infant monocytes and neutrophils (18). However, this would first require modification and optimization of the methodologies used, in order to ensure they are compatible with the very small postnatal blood volumes available from extremely preterm infants.…”
Section: Phagocytosis In Newborn Whole Bloodmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the pH of S. Typhimurium SCVs was performed according to a previous report (Wong et al, 2011). Bacteria were either dually labelled with a pH-sensitive probe (pHrodo, which emits red fluorescence in an acidic environment; Invitrogen) and a pH-insensitive probe Alexa Fluor 488 (green) or singly with pH-sensitive FITC as described previously (Bernardo et al, 2010). The calculated fluorescence ratios of pH-sensitive and pH-insensitive probes (in the dual-labelling process) and mean fluorescence intensity (in the single-labelling process) were used to determine phagosomal pH according to a calibration curve.…”
Section: Methodsmentioning
confidence: 99%